Antioxidant and antimicrobial properties of Litsea elliptica Blume and Litsea resinosa Blume (Lauraceae) - Mui-Hung Wong; Li-Fang Lim; Fasihuddin bin Ahmad; Zaini bin Assim (Asian Pacific Journal of Tropical Biomedicine, 2014)
Objective: To investigate antioxidant and antimicrobial activities of two plant species, Litsea elliptica (L. elliptica) and Litsea resinosa (L. resinosa). Methods: In vitro method -2,2-diphenyl-1-picrylhydrazyl radical scavenging assay was conducted for antioxidant activity determination while antimicrobial assay consisted of agar well diffusion assay and mycelial radial growth assay. Results: Methanol extracts of root and stem of L. elliptica and L. resinosa exhibited the highest antioxidant activity with EC50 of 23.99, 41.69, 11.22 and 35.48 mg/L respectively. All methanol extracts of L. resinosa as well as root extracts from L. elliptica showed significant scavenging activity. Hexane extract from stem of L. resinosa presented the largest inhibition zone in Gram-negative bacteria Pseudomonas aeruginosa and Escherichia coli while chloroform extract from inner bark of L. resinosa showed major inhibition towards Gram-positive bacteria Bacillus subtilis. Essential oils from the root of both species showed significant antifungal activities which are 80.11% and 66.85% respectively. Conclusions: Overall, methanol extracts from root and stem of both species showed antioxidant activity comparable to standard butylated hydroxytoluene. Extracts from L. resinosa demonstrated stronger antimicrobial properties compared to that from L. elliptica.